Colhe Aí: An Application for Irrigation Control and Soil Monitoring System - Martins, Bianca; Barros, Raíssa; Mesquita, Cecília; C. Neto, Francisco; Lopes, Ana Lívia; Martins, Andressa; Libório, Andréia; Silva, Marcelo Martins da (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2025: Companion Proceedings of the 21st Brazilian Symposium on Information Systems, 2025)
It is estimated that 70% of all water used in agriculture is wasted due to a lack of control over the amount of water used. Therefore, smart agriculture seeks to help farmers in assessing production conditions. The present work aims to present Colhe aí, an irrigation assistance system for farmers based on an application and an embedded system for managing soil and its resources.